Poetics of Praise: Love and Authority in al-ḤājjʿUmar Tāl’s Safīnat al-saʿāda li-ahl ḍuʿf wa-l-najāda - Syed, Amir (Islamic Africa, 2016)
In this article, I provide one example of how a careful engagement with poetry can enrich our understanding of West African history. In 1852, al-ḤājjʿUmar Fūtī Tāl (d.1864) completed his panegyric of the Prophet Muḥammad—Safīnat al-saʿāda li-ahl ḍuʿf wa-l-najāda or The Vessel of Happiness and Assistance for the Weak. Through an analysis of Safīnat al-saʿāda, I explain Tāl’s creative use of two older poems that were widespread in West Africa—al-ʿIshrīniyyāt—The Twenties—of ʿAbd al-Raḥmān al-Fāzāzī (d. 1230), and its takhmīs (pentastich) by Abū Bakr ibn Muhīb (n.d.). Though Safīnat al-saʿāda was primarily meant for devotion, it also reflected Tāl’s scholarly prestige and claims he made about his religious authority. In the long prose introduction to the poem, Tāl claimed that he was a vicegerent of the Prophet, and therefore had authority to guide and lead the Muslims of West Africa. His composition of Safīnat al-saʿāda was partly meant to prove this point.